Factors associated with self-medication practices of primary dysmenorrhea among students - Sembiring, Ernesta Br.; Siburian , Friska Lasro Yanti; Suci, Tri; Ginting, Astriani Natalia Br (Buletin Kedokteran & Kesehatan Prima, 2025)
Self-medication and home remedies are the most frequently used methods to relieve menstrual discomfort among female college students. The practice of self-medication varies among adolescent female students. Therefore, this study aimed to observe and analyze the factors associated with the practice of self-medication for primary dysmenorrhea among university students.This study used an analytical observational design with a cross-sectional approach, involving 207 female health students from Universitas Prima Indonesia. The sample was obtained through a purposive sampling technique. Data analysis included univariate analysis, bivariate analysis (chi-square and Fisher's exact test), and multivariate analysis (logistic regression). The prevalence of self-medication was reported to be 36.7%. Several factors were found to be associated with self-medication practices for primary dysmenorrhea among students, namely menstrual cycle (p<0.001, OR: 3.27, 95% CI 1.75-6.10), duration of pain during menstruation (p<0.001 OR: 3.85, 95% CI 2.10-7.07), and severity of pain (p=0.009 OR: 2.21, 95% CI 1.24-3.93). In contrast, age (p=0.316), academic year (p=0.889), family history (p=0.470), age at menarche (p=0.223), and menstrual duration (p=0.552) did not show a statistically significant association with self-medication practices for primary dysmenorrhea. The dominant factor influencing self-medication practices for primary dysmenorrhea was pain duration. Notably, self-medication with medications was found to be relatively low among health students with primary dysmenorrhea. Therefore, educational programs that address the limitations of self-medication with drugs need to be implemented effectively.